Activity Report: “Gender disaggregated CSA adoption trends: Results from two different surveys in Tuma-La Dalia in Nicaragua” - Arora, Diksha (2019)
In this paper, we present the gender disaggregated adoption and implementation patterns of different adaptation practices by rural communities in Tuma-La Dalia in Nicaragua. The analysis considers gender differences in knowledge, sources of information and intra-household dynamics related to adoption of CSA and other adaptive practices. We present results from a baseline survey of intra-household aspects of farming households conducted in Tuma La Dalia during September and October 2015 and from CSA monitoring survey conducted in the same site during 2018. The results of this paper analyze the socio-economic factors motivating and constraining adoption of practices. The paper presents the existing patterns of adoption, sources of information and decision-making related to adoption, and recommends ideas and methods for improving data collection to construct a framework to analyze gender-sensitive determinants of adoption.